Flexible manufacturing systems decision support for design and operation - Tempelmeier, Horst 1952-; Kuhn, Heinrich 1959- (Wiley, 1993)
Now, this comprehensive and systematic overview of both the design models and quantitative solution methods for FMS support, configuration, and operation rectifies that problem. Students, production managers/planners, and FMS installation planners can now find everything they need in one authoritative and up-to-date source
Keywords: Automacao, robotica e cad/cam (engenharia mecanica); Fabrication, Systèmes flexibles de - Planification; Flexibele productiesystemen; Flexible manufacturing systems -- Planning; Flexible Fertigung; Systemplanung